Iklim Organisasi dan Motivasi Kerja Pada Universitas Batanghari Jambi - Saiyid Syekh; Ali Akbar; Muhammad Syukri (Universitas Batanghari Jambi, 2020)
This study aims to determine the effect of leadership style and organizational climate on the performance of lecturers at Batanghari University, Jambi. This study uses a quantitative approach with the form of correlational research which explains the relationship of each independent variable with the dependent variable, either individually or collectively, and makes predictions for the dependent variable on each independent variable. With the regression equation Y = 3,120 + 0.453 X1 + 0.494 X2 + 0.010 X3 From the above equation, it can be seen that if the leadership style can be more effective by one unit, the lecturer performance will increase by 0.453; Likewise with the organizational climate, if the organizational climate is better by one unit, the lecturer's performance will increase by 0.494, something that is not much different from motivation, namely if the motivation is increased by one unit, the performance will increase by 0.010. This means that leadership style, organizational climate and motivation have a positive correlation with lecturer performance. Therefore, it is expected that these three components (X1, X2 and X3) can be optimally improved. The results of simultaneous hypothesis testing show that the value of F count is 33.110 at the level of freedom of 95 and α = 5% greater than F table 2.02439. or sig F 0.000 <0.05, this means that simultaneously or collectively, leadership style, organizational climate and motivation have a significant effect on lecturer performance at the University of Batanghari Jambi.